2001
DOI: 10.1063/1.1352042
|View full text |Cite
|
Sign up to set email alerts
|

Multistage, monolithic ceramic microdischarge device having an active length of ∼0.27 mm

Abstract: A three-stage, multilayer ceramic microdischarge device, having an active length of ∼267 μm and a cylindrical discharge channel 140–150 μm in diameter, has been developed and operated continuously in Ne gas. Stable glow discharges are produced for pressures above 1 atm, operating voltages as low as 137 V (at 800 Torr), and specific power loadings of ∼40 kW cm−3. The V–I characteristics for a fired ceramic structure exhibit a negative resistance, whereas the resistance is positive prior to firing. The manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…38). A ceramic structure with three microdischarge cells in series was successfully operated in Ne by Vojak et al [113].…”
Section: Series Operation Of Microcavity Dischargesmentioning
confidence: 99%
“…38). A ceramic structure with three microdischarge cells in series was successfully operated in Ne by Vojak et al [113].…”
Section: Series Operation Of Microcavity Dischargesmentioning
confidence: 99%
“…Devices which have been built include proximity sensors, gas flow sensors, electrochemical sensors, and pressure sensors. Vojak et al created a ceramic microdischarge device with LTTC technology, housing a stable Ne-discharge in a cylindrical cavity of 140 lm diameter and 230 lm length at a voltage of 137 V. [63] For organic synthesis, a ceramic microreactor for the methoxylation of methyl-2-furoate has been demonstrated. [64] Finally, Wilcox et al demonstrated that the technology is mature by integrating a PEM (polymer electrolyte membrane) fuel cell design including methanol gas reforming.…”
Section: Meso-scaled Devices Based On Co-fired Ceramic Tape Technologymentioning
confidence: 99%
“…Recently, Vojak et al 5 described the characteristics of single, ϳ150 m diam microdischarge devices fabricated in a multilayer ceramic structure. Ceramic is of interest for two primary reasons: ͑1͒ its suitability for high temperature operation and aggressive chemical environments, and ͑2͒ the existing commercial investment in ceramic multilayer technology, driven by wireless and microfluidics systems applications, which has resulted in a versatile platform for integrating electronic, mechanical, and optical components.…”
mentioning
confidence: 99%